Advantages and advantages of binders of low water demand - Muzaffar Safarovich Makhammatov (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The advantage and advantage of binders of low water demand (VNV) are in their high dispersion, in very high strength (up to 100 MPa). This is achieved due to the content in large quantities of superplasticizer C-3.